Bandwidth Broker Architecture for Diffserv Networks - Octavian Pop; Tamas Mahr; Tímea Dreilinger; Robert Szabo (Communications - Scientific letters of the University of Zilina, 2001)
A Bandwidth Broker (BB) is an automated resource manager in the Differentiated Services architecture. It manages Quality of Service resource allocation requests within a single or successive DiffServ domains based on the available resources and on the Service Level Agreements formerly negotiated between the customer and its service provider. If used for multi-domain resource management, BBs negotiate among each other on behalf of the service initiator. Additionally, BBs also participate in transit domain communication by coordinating SLAs across domain boundaries. Various BB architectures have been proposed in the recent years, some of them even have been implemented, but all of them are in a preliminary stage or do not address important issues such as bi-directional resource allocation. In this paper we propose a BB architecture that includes policy manager functions for authorization, supports quantitative and qualitative services, handles bi-directional resource allocation and features a vendor-independent resource allocation approach, i.e., neither software nor hardware modification of core routers are required.